Constantine : distorted illusions - Garcia, Kami (DC Comics, 2022)
John Constantine, a magician of the highest caliber, accepts an apprenticeship in the United States to become the lead singer of his best friend's punk band, but when a complicated spell gets out of hand, the disastrous consequences might be more than Constantine can handle.